Can the concept of nutrient density be useful in helping consumers make informed and healthier food choices? A mixed‐method exploratory approach. Issue 3 (15th August 2021) - Spiro, Ayela; Wood, Victoria
Abstract: Poor dietary patterns are major risk factors for chronic diseases and pose a challenge to public health. Strategies to achieve dietary improvement are likely to be complex and multifactorial, but of interest is whether the concept of nutrient density, paying attention to intakes of multiple essential nutrients within appropriate energy balance, could be a worthwhile approach, and whether this could help in the communication of healthier dietary patterns to consumers. In order to explore the concept further, a mixed‐methods market research approach was undertaken, using in‐depth interviews and surveys with consumers and nutrition professionals. This produced some rich insights into the way consumers perceive the nutrient quality of their diets. There was a notable desire amongst both groups to support a move away from concentrating on single nutrients and calories to a broader, more holistic approach that incorporates some of the positive nutritional aspects of foods. Overall, the concept of nutrient density was recognised as a helpful tool in describing healthier foods and nutritional quality. However, the actual term 'nutrient density' is unfamiliar to consumers, and communicating nutrient density to consumers who have different understandings, beliefs and motivations may be challenging. Further research is needed to identify how to best frame the concept in a way that resonates with consumers and facilitates dietary behaviour change.